2016
DOI: 10.1103/physrevlett.116.056401
|View full text |Cite
|
Sign up to set email alerts
|

Simple Screened Hydrogen Model of Excitons in Two-Dimensional Materials

Abstract: We present a generalized hydrogen model for the binding energies (EB) of excitons in twodimensional (2D) materials that sheds light on the fundamental differences between excitons in two and three dimensions. In contrast to the well-known hydrogen model of three-dimensional (3D) excitons, the description of 2D excitons is complicated by the fact that the screening cannot be assumed to be local. We show that one can consistently define an effective 2D dielectric constant by averaging the screening over the exte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
239
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(263 citation statements)
references
References 30 publications
24
239
0
Order By: Relevance
“…This is the so-called Mott-Wannier model which has been instrumental in the description of excitons in inorganic bulk semiconductors. A 2D version of the Mott-Wannier model has recently been shown to yield exciton binding energies in good agreement with BSE calculations and experiments for both freestanding [15,16,18,19,28] and supported [15,28,29] transition-metal dichalcogenide layers. The dissociation rate of the exciton is then obtained by complex scaling, which is a formally exact technique to compute resonance energies and lifetimes.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…This is the so-called Mott-Wannier model which has been instrumental in the description of excitons in inorganic bulk semiconductors. A 2D version of the Mott-Wannier model has recently been shown to yield exciton binding energies in good agreement with BSE calculations and experiments for both freestanding [15,16,18,19,28] and supported [15,28,29] transition-metal dichalcogenide layers. The dissociation rate of the exciton is then obtained by complex scaling, which is a formally exact technique to compute resonance energies and lifetimes.…”
mentioning
confidence: 61%
“…Recently, it has been shown that excitons in 2D materials can be described by a 2D hydrogen model with an effective dielectric constant [28], which for the linear screening described by Eq. (2) is given by eff = 1 2…”
Section: -2mentioning
confidence: 99%
“…The bare Fröhlich interaction strengths obtained via ab initio techniques give 334 mev (MoS 2 ), 500 meV (MoSe 2 ), 140 mev (WS 2 ) and 276 meV (WSe 2 ) [70], hence the Molybdenum-based TMDCs possess higher exciton-phonon coupling strengths than the Tungsten-based TMDCs. A precise estimate of the exciton binding energy in the monolayer TMDCs is not available, however a range of binding energies (100 to 800 meV) have been reported for the monolayer systems [6,8,11,64,[64][65][66][78][79][80]. In order to compare the exciton formation rates between Molybdenum-based TMDCs and Tungsten-based TMDCs, we make use of the effective masses of electron and holes at the K energy valleys/peak position given in Ref.…”
Section: Exciton Formation Times For Other Exemplary Monolayer Tmentioning
confidence: 99%
“…These materials have intriguing electronic and optical properties and serve as versatile building blocks in van der Waals stacked devices [1][2]. The linear and nonlinear optical properties of semiconducting TMDs are dominated by excitons [1][2][3][4][5][6]. In monolayer structures with little substrate screening, the exciton binding energy is as large as 0.5 eV [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%